포천지역 초기 조림지 탄소저장량 추정을 위한 소나무 조림목 바이오매스 상대생장식 개발 - 송규홍; Kyu Hong Song; 장지원; Ji Won Jang; 이세희; Se Hee Lee; 이상태; Sang Tae Lee; 정상훈; Sang Hoon Chung; 노남진; Nam Jin Noh (한국산림과학회지, 2025)
본 연구는 소나무(Pinus densiflora) 초기 조림목의 바이오매스 상대생장식을 개발하고 초기 조림지의 탄소 저장량을 추정하기 위해 수행되었다. 2024년 4월, 7년생 소나무 조림지 내에 정방형 조사구 9개를 설치하고 조사구 내 조림목들을 대상으로 매목조사를 실시하였다. 10월에 소나무 조림목 16본을 선정하여 근원경, 흉고직경, 수고, 수관폭을 재측정한 뒤, 뿌리를 포함하여 수확하였다. 소나무 조림목의 바이오매스 추정 모델의 적합성은 근원경 기반(R²>0.96), 수관폭 기반(R²>0.91), 흉고직경 기반(R²>0.88) 모델 순으로 높게 나타났다. 소나무 조림목의 부위별 바이오매스 구성비는 줄기가 17.5%, 가지28.5%, 잎 36.4%, 그리고 뿌리 17.6%로, 성숙목에 비해 가지와 잎이 높은 비율을 차지했다. 본 연구에서 개발된 바이오매스상대생장식과 매목조사를 바탕으로 추정된 소나무 초기 조림지의 탄소저장량은 5.25±0.42 Mg C ha -1 로 나타났다. 본 연구에서 개발된 소나무 어린나무의 바이오매스 상대생장식은 소나무 재조림지와 산림 복구지의 초기 탄소 저장량과 흡수량을 보다 정확히 추정하는 데 기여하며, 이를 바탕으로 입지 생산성을 정량적으로 평가하는 데 중요한 자료를 제공한다. This study aimed to develop biomass allometric equations for Pinus densiflora saplings to assess carbon storage in young plantations. In April 2024, nine sample plots were established in a 7-year-old pine stand, and a tree census was carried out within each plot. In October, 16 saplings were selected for destructive sampling. Prior to harvesting, measurements of root collar diameter (RCD), diameter at breast height (DBH), height, and crown width (CW) were repeated for each sapling, and the entire tree, including its root system, was collected. Among the developed models for biomass estimation, the RCD-based model demonstrated the highest explanatory power (R² > 0.96), followed by the CW-based model (R² > 0.91) and the DBH-based model (R² > 0.88). The biomass allocation by component was 17.5% in stems, 28.5% in branches, 36.4% in foliage, and 17.6% in roots, with branches and foliage accounting for a higher proportion compared to mature trees. Using the biomass equations and census data, carbon storage in early-stage plantations was estimated at 5.25 ± 0.42 Mg C ha -1 . These equations support more accurate estimations of carbon storage and sequestration in pine reforestation and restoration efforts, offering critical data for evaluating forest productivity.